2022
DOI: 10.1108/jtf-03-2021-0072
|View full text |Cite
|
Sign up to set email alerts
|

Augmented reality adoption intention among travel and tour operators in Malaysia: mediation effect of value alignment

Abstract: PurposeThis study evaluated the determinants of augmented reality (AR) adoption in Malaysia's travel and tour operator sectors through an integrated technology-organization-environmental (TOE) and diffusion of innovation (DOI) model.Design/methodology/approachThe TOE and DOI were considered the primary theoretical models but are combined and extended by including few additional variables. Data were collected from 220 respondents of travel and tour operating businesses in Malaysia and analyzed by applying PLS s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 89 publications
2
17
0
Order By: Relevance
“…Considering Study F, the results found that RA significantly impacts BI. On the contrary, TRI (provides opportunities to try various FinTech services, helps in getting benefits of innovation before final decision and trial FinTech services help in reduce uncertainties) has an insignificant impact on BI, which is consistent with the finding of Alam et al (2022) concluded that trial facility significantly reduces technological uncertainty.…”
Section: Discussionsupporting
confidence: 81%
“…Considering Study F, the results found that RA significantly impacts BI. On the contrary, TRI (provides opportunities to try various FinTech services, helps in getting benefits of innovation before final decision and trial FinTech services help in reduce uncertainties) has an insignificant impact on BI, which is consistent with the finding of Alam et al (2022) concluded that trial facility significantly reduces technological uncertainty.…”
Section: Discussionsupporting
confidence: 81%
“…Augmented reality (AR) is a “computer-generated object that improves the real-world environment, offering context-sensitive information about the user's close surroundings in the combination of image, 3D models and immersive features using the technological appliance, that is, eyeglasses, a desktop, tablet and a smartphone” (Alam et al. , 2022, p. 1, Yung and Khoo-Lattimore, 2019).…”
Section: Technologies Influencing the Vcc Processmentioning
confidence: 99%
“…Compatibility was discovered to be the main factor influencing technology (Lubanga et al, 2017;Nezamdoust et al, 2022). In light of this, compatibility may be used as an independent variable to help determine the degree of adoption at the governmental level, acting as an early warning system for its high relevance (Alam et al, 2022;Erdener et al, 2022).…”
Section: Discussion Of Resultsmentioning
confidence: 99%